The Quest for Prosperity: How Developing Economies Can Take Off - JUSTIN YIFU LIN (Princeton University Press, 2014)
Since becoming the World Bankâ€™s chief economist, I have had ample opportunity to reflect on an old American saying: â€œBe careful what you wish for, you might just get it!â€ For better or worse, the beginning of my tenure coincided with the eruption of the most serious financial and economic crisis, both in magnitude and in scope, since the Great Depression. No country has been immune to the economic slowdown. Most economic and financial experts severely underestimated its timing, speed, and severity. As a result, despite strong macro policy responses, the current situation remains full of uncertainties. This crisis, unlike many other crises preceding it, was not the fault of developing countries. It was an unexpected setback to and challenge for their macro management. Some of them had little exposure to the financial derivatives that triggered the crisis and had the fiscal space and the foreign reserves to apply strong policy stimulus programs. But many others had enormous short-term capital inflows through multinational bank branches, large current account deficits, overpriced housing markets, or limited fiscal space for countercyclical measures The amplitude, brutality, and unfairness of the crisis was perhaps most obvious in Sub-Saharan Africa. Despite being the global economyâ€™s least integrated region, it was perhaps the worst hit by the crisis. Each channel for the crisis to affect the continent has had a particularly nefarious impact. The decline in commodity prices, though a benefit to oil-importing countries, has led to a substantial decline in exports and government revenue for many commodity exporters. Even countries that saved their windfalls when prices were high suffered because their nonoil sectors are small and highly dependent on government spending.Private capital flows, which had surged to record levels prior to the recession (and exceeded foreign aid to the continent) declined abruptly. African stock markets fell by an average of 40 percent, with some, such as that of Nigeria, falling by more than 60 percent.2 Workersâ€™ remittances, which had also been on the rise and had become a major source of growth for laborexporting countries, also declined substantially. Only foreign aid continued to rise, but it remained well short of the commitments made by G-8 countries at the Gleneagles Summit in 2005, when the global economy was more robust. With mounting pressures in donor countries to stimulate their own economies and plan for fiscal consolidation, it could be expected that the volumes of aid they gave to Africa would be lower in the years ahead. Such developments were likely to slow their growth rates and derail progress toward the Millennium Development Goals.3 Luckily, through a joint effort, the world has avoided the worst. Policymakers quickly understood the almost unprecedented scale and dangers of the crisis. Other postâ€“World War II economic crises occurred either in some individual developing country or region (East Asia, Latin America, Mexico, or the Russian Federation) or in only one or two high-income countries (Japan, Sweden). Their impact was a small fraction of global GDP. This time, the crisis struck almost all advanced and developing economies at the same time, making it impossible for one country to escape high unemployment and large excess capacity through individual actions on monetary, exchange rate, or trade policies.